Measuring Career Aspirations of Women Workforce in the Banking Sector in Nepal - Indira Shrestha, (Pravaha, 2024)
Measuring the career aspirations of women in Nepalese banking sector was the objective of the study. The study's population were women who worked in Nepali commercial banks as supervisors or higher. A sample size of 319 women was used for the research. Information was gathered via a questionnaire that included 18 statements about women's career aspirations. Women's career aspirations were measured using a descriptive research approach. The data was described by mean percentage, frequency, and standard deviation. Women moderately agreed that they do not aspire to careers in organizations because they are family-focused, shun risky occupations, lack advocacy, lack ambition, want high job security and fewer challenges, according to the overall mean score of their career aspirations. The study's findings will help them stay informed about their professional goals and areas that require attention if they wish to advance in their careers.